The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/0102-311x00136313
|View full text |Cite
|
Sign up to set email alerts
|

Las denuncias de los afiliados de las empresas de medicina prepaga presentadas ante la Subsecretaría de Defensa del Consumidor en Argentina, 2000-2008

Abstract: El trabajo analiza los problemas de los afiliados a las empresas de medicina prepaga en Argentina cuando las mismas incumplen con la Ley de Defensa del Consumidor. El universo de estudio se conformó por las denuncias de los afiliados durante los años 2000-2008, ante la Subsecretaría de Defensa del Consumidor de la Nación, y por las disposiciones y laudos emitidos por la misma. Un aspecto conclusivo es la recurrencia de los incumplimientos en las prestaciones del Programa Médico Obligatorio y los argumentos exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The search strategy resulted in 117 scientific productions (according to Figure 1), which made it possible to have as product 14 tracked studies, assessed for readability and included in the research, which comprise 100% of the sample, as shown in Chart 1, named "articles included in the study". Such chart brings the variables: item; year; title of the scientific productions identified by PC 1 (12) , PC 2 (13) , PC 3 (14) and so on until PC15 (26) , with the proviso that the PC 2 (13) , Luzuriaga (13) (2014), was excluded for showing an international character in its objects; author and origin, distinguished by superscript number from 12 to 26 (with emphasis on the fact that the number 13 corresponded to PC 2); journal; objective; and type of study or methodological approach. Thus, the data confirm the information of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy resulted in 117 scientific productions (according to Figure 1), which made it possible to have as product 14 tracked studies, assessed for readability and included in the research, which comprise 100% of the sample, as shown in Chart 1, named "articles included in the study". Such chart brings the variables: item; year; title of the scientific productions identified by PC 1 (12) , PC 2 (13) , PC 3 (14) and so on until PC15 (26) , with the proviso that the PC 2 (13) , Luzuriaga (13) (2014), was excluded for showing an international character in its objects; author and origin, distinguished by superscript number from 12 to 26 (with emphasis on the fact that the number 13 corresponded to PC 2); journal; objective; and type of study or methodological approach. Thus, the data confirm the information of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…In health services, N is 8, totaling 100%, considering eight items considered in Figure 2, subdivided in: medications; hospital beds for hospitalization in a ward or ICU; diagnostic and surgical procedures; general and specialized consultations; food formulas; and diapers. The other Ns, equal to 1, represent 100% and refer to resource allocation, function and interconnection between the three powers (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) .…”
Section: Documentary Studymentioning
confidence: 99%